SUFISM VALUES IN THE WORKPLACE AS RESILIENT EMPLOYEES DURING A CRISIS - Cintami Farmawati; Annisa Mutohharoh; M.Z. Abdullah (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2023)
Resilience is a person's ability to recover from crises and challenges encountered in life. Sufism or Sufistic values ​​in the workplace for employees on a regular basis can ensure employee resilience remains safe, good and effective during crisis situations due to the COVID-19 pandemic. This research aims to find out how the values ​​of Sufism work in the workplace as resilient employees during the crisis. This research is qualitative research. The subjects in the research were 3 employees who worked in the office during the crisis. Data collection methods use interviews and observation. The data analysis used is data reduction, data presentation, and drawing conclusions. The research results show that Sufism values ​​in the workplace can function as a foundation for the growth of a positive mentality and morality for resilient employees during a crisis. Sufism values ​​contain Illahiyah (divinity) values; second, Insaniyah (humanity) values; and the third is the Alamiyah (naturalness) values which of course are really needed by employees to remain resilient in difficult situations. Employee resilience during the COVID-19 pandemic crisis includes self-efficacy, emotional regulation, impulse control, empathy and optimism in carrying out work in the office during the COVID-19 pandemic.